Understanding and Interpretation of Indonesian Museum Collections on Culture And People in The Archipelago - Awaloedin, Dipa Teruna; Pradini, Gagih; Agustiani, Fitri; Salsabila, Khania Fasha; Fatimah, Dinda Putri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Museum Indonesia is one of the many museums in Taman Mini Indonesia Indah. This Indonesian Museum is an anthropology museum where in this museum there is knowledge about culture and humans, especially humans in the archipelago. Cultural tourism is part of tourism as a whole. Cultural tourism deals with a region's culture, lifestyle, history, art, architecture, religion and other elements that makeup residents' way of life in a geographical area. This article will discuss the understanding and interpretation of culture and humans in Nusantara, Indonesia.